Peran Ijtihad dalam Menjawab Tantangan Hukum Islam di Era Modern - Amalia Azahra; Fadhil Muhammad Dzaki; Robbi Hardiansyah Manik; Juanda Pramu Yudistira; Wismanto Wismanto; Fitria Mayasari (Journal of Student Research, 2025)
Ijtihad as a methodology for formulating Islamic law is an important approach in understanding and developing Islamic law. This journal discusses the definition of ijtihad, the basics of ijtihad, and its role in the context of social change and community needs. The purpose of this study is to see and explore how far our understanding of the role of ijtihad in responding to the challenges of Islamic law in the global era. This study uses a qualitative method by making books, magazines, articles, journals related to the research theme as the main reference in collecting data to be codified and then poured into a description. The results of the study show that ijtihad is not just reasoning, but also involves a deep understanding of legal sources such as the Qur'an and Hadith. In addition, this article describes the challenges and opportunities faced by mujtahids in the modern era, as well as the importance of ijtihad in overcoming contemporary problems. Thus, ijtihad is expected to contribute to producing laws that are relevant and responsive to the dynamics of society.